2013
DOI: 10.1128/mcb.00874-13
|View full text |Cite
|
Sign up to set email alerts
|

hMOF Acetylation of DBC1/CCAR2 Prevents Binding and Inhibition of SirT1

Abstract: The NAD؉ -dependent deacetylase SirT1 regulates gene silencing and genomic stability in response to nutrient deprivation and DNA damage. An important regulator of SirT1 in mammalian cells is DBC1 (deleted in breast cancer 1; KIAA1967 or CCAR2), which binds to SirT1 and inhibits the deacetylation of substrates. Recent studies have revealed that ATM/ATR-mediated phosphorylation of DBC1 promotes binding to SirT1. Here we show that DBC1 is modified by acetylation on two N-terminal lysine residues (K112 and K215). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 39 publications
2
31
0
Order By: Relevance
“…Recent studies have revealed that ATM/ATR-mediated phosphorylation of DBC1 promotes binding to SirT1 [ 34 ]. Phosphorylation of RUNX1 by CDK reduces direct interaction with HDAC1 and HDAC3 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed that ATM/ATR-mediated phosphorylation of DBC1 promotes binding to SirT1 [ 34 ]. Phosphorylation of RUNX1 by CDK reduces direct interaction with HDAC1 and HDAC3 [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoprecipitation (IP) methodologies were as reported for endogenous proteins (10,11), or Myc-, GST-, and HA-tagged proteins (5,(25)(26)(27).…”
Section: Pulldown Assaysmentioning
confidence: 99%
“…Acetylation sites on CCAR2 were identified following the general approach reported previously (5). In brief, 24 hours after seeding, HCT116 cells were treated with sulforaphane or DMSO, and 6 hours later the cell lysates were subjected to IP using CCAR2 antibody.…”
Section: Mass Spectrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…To prevent these detrimental consequences, eukaryotic cells have evolved an elaborate and complex response system called DNA damage response (DDR), which is mostly initiated by the phosphatidylinositol 3-kinase (PI3)-like family of kinases, including DNA-dependent protein kinase (DNA-PK) catalytic subunit, ataxia telangiectasia mutated (ATM), and ataxia telangiectasia-and Rad3-related (ATR) ( Ciccia and Elledge, 2010 ; Lee and Chowdhury, 2011 ; Matsuoka et al, 2007 ; Mu et al, 2007 ; Smith et al, 2010 ). Recently, DBC1 (also named p30 DBC, KIAA1967, or CCAR2) was identified as a new target of ATM/ATR kinases ( Zannini et al, 2012 ) and it plays a critical role in maintaining genomic stability and cellular integrity following genotoxic stress ( Kim et al, 2008 ; 2009a ; Magni et al, 2014 ; Park et al, 2014 ; Zannini et al, 2012 ; Zheng et al, 2013 ). Upon DNA damage conditions, DBC1 on Thr454 is phosphorylated, which promotes acetylation-mediated p53 activation through inducing the interception of NAD-dependent deacetylase sirtuin-1 (SIRT1) from p53 and triggers apoptosis.…”
Section: Introductionmentioning
confidence: 99%